Adenomatoid odontogenic tumor - a rare cause of jaw swelling - Nigam,Sonu (2005)
Adenomatoid odontogenic tumor (AOT) is an uncommon tumor of odontogenic origin, characterized histologically by the formation of ductlike structures with amyloid-like deposits. Histogenesis of AOT is still uncertain and it is often considered as a hamartomatous lesion rather than a true neoplasm. AOT has a benign behavior and conservative surgical enucleation or curettage is sufficient. We report a case of AOT in a 15-year-old female who presented with left-sided jaw swelling with tooth resorption. Histopathology revealed intraosseus follicular variant of AOT. A brief review of literature is also discussed.